(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To describe the case of longitudinal structural changes in the optic disc in ischemic optic neuropathy. Methods: A 63-year-old male patient (two eyes) was under observation for three months, from August to October 2024. Informed consent to use medical records for research purposes was obtained from the patient. Ethical approval was obtained from the local ethics committee (committee meeting minutes of March 24, 2022). Visual acuity and ophthalmoscopy OU were done and optic coherence tomography (OCT) OS was performed in August and October, 2024, and OCT OD was performed in October, 2024. Automated perimetry and OCT angiography (OCTA) OU were performed in October, 2024. Results: The 63-year-old male patient was examined and diagnosed with “optic atrophy OS and non-arteritic ischemic optic neuropathy (NAION) OU”. The OCT study of structural components of the optic disc OS showed a 54.9% reduction in the average thickness of retinal nerve fiber layer (RNFL) of the optic disc and a 4.4% reduction in the thickness of the inner retinal complex (GCL++) in October compared to August 2024. In August 2024, RNFL thickness and GCL++ thickness in the superior and inferior segments were thicker in the left eye than in the right eye. In October 2024, the thickness of both layers in the inferior segment became thicker than the thickness of the superior segment for the left eye, likely reflecting the expansion of swelling to the inferior segment. In October 2024, it was in the inferior segment of the peripapillary region that OCTA showed a reduction in vessel density along with dilated and tortuous capillaries. Conclusion: Studies of longitudinal structural changes in the optic disc reflect the role of localized swelling as a consequence of impaired blood perfusion in NAION, and confirm an increase in the affected area, likely due to secondary factors.